IMPROVING BIOLOGY LEARNING ACHIEVEMENT ON "CELL" MATERIAL THROUGH THINK-PAIR-SHARE OF STUDENTS IN CLASS XI MIA-2 SMA NEGERI 21 SURABAYA - Rusdiana Halim (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2023)
This research, which is designed as a three-cycle class action research, aims to describe (1) the process of improving the learning outcomes of students in class XI MIA-2 SMA Negeri 21 Surabaya Even Semester of the 2021/2022 academic year on Cell material through the think pair share learning model, (2) describe the results of improving the learning outcomes of students in class XI MIA-2 SMA Negeri 21 Surabaya Even Semester of the 2021/2022 academic year on Cell material through the think pair share learning model, and (3) determine the response of students in class XI MIA-2 SMA Negeri 21 Surabaya Even Semester of the 2021/2022 academic year to the application of the think pair share learning model to improve learning outcomes on Cell material. The results of the research on student learning completeness showed that the Think Pair Share model had a positive impact in improving the quality of student learning which was marked by an increase in student learning completeness in each cycle, namely in cycle I of 66.7%, cycle II of 80.6%, and cycle III of 94.4%. The evaluation results also showed an increase. In Cycle I it was 66.7, Cycle II 76.9, and in Cycle III it was 80.0. The results of research on teacher and student activities in the most dominant learning are working with tools / media, listening / paying attention to teacher explanations, and discussions between students / between students and teachers. So it can be said that student activities can be categorized as active. Meanwhile, the teacher's activities during learning have carried out the steps of the Think Pair Share model cooperative learning method well. It can be seen from the teacher's activities that appear, including the activities of guiding and observing students in working on LKS activities/finding concepts, explaining difficult material, giving feedback/evaluation/question and answer, the percentage of which is quite large. Thus, it can be concluded that the Think Pair Share model has a positive impact in improving the quality of student learning and student learning motivation. For this reason, it is recommended to teachers, especially Biology teachers, to apply the think pair share learning model as an alternative to innovative learning